‘Doing the best we can’: Registered Nurses' experiences and perceptions of patient safety in intensive care during COVID-19 - Stayt, LC; Merriman, C; Bench, S; Price, AM; Vollam, S; Walthall, H; Credland, N; Gerber, K; Calovski, V (Wiley, 2022)
Aims To explore registered nurses' experiences of patient safety in intensive care during COVID-19.